NUMBER OF RENAL ECHOGENIC FOCI IN PATIENTS OF FATTY LIVER IN RELATION WITH DIABETES: Renal Echogenic FOCI in Fatty Liver of Diabetes - Anwar, Javed; Tahir, Muhamamd (Pakistan Armed Forces Medical Journal, 2016)
Objective: To establish a relationship of numbers of renal echogenic foci and the grades of fatty liver with the time span of diabetes mellitus.Study Design: Cross sectional study.Place and Duration of Study: Radiology Department of Combined Military Hospital (CMH) Kohat from 1st January 2014 to 1st May 2014.Material and Methods: Patients reporting for ultrasound abdomen in Radiology Department at CMH Kohat and showing renal echogenic foci i.e. bright foci without significant distal acoustic shadowing and fatty liver were selected and included in this study. Forty (40) patients were selected in the study by non probability purposive sampling and these were categorized into three groups according to the number of renal echogenic foci i.e. those with less than 5 were grouped as REF 1, those with 5-10 as group REF-2 and those with more than 10 foci as group REF-3. Patients having associated fatty liver that is those showing bright liver along with vascular blurring in liver parenchyma were grouped as mild, moderate and severe depending upon the ultrasound attributes of fatty liver (FL). The clinical and demographic variables were laid down. All of the patients were subsequently subjected to fasting blood sugar levels and glycated hemoglobin HBA1C with their consent. The patients having normal fasting blood sugar le els (3.3-5.6 mmol/L) were excluded from the study. These cases were grouped according to the HbA1C levels i.e. 5.6-6.8%, 6.8%-7.6% and >7.6% as good, fair or poor control patients respectively. Data was analyzed by SPSS version 20.Results: Average age of patients included in the study was 48.62 years (SD=10.43) with 70% female patients. Twenty four (60%) patients had mild FL, 14 (35%) patients had moderate FL and 2 (5%) patients had severe FL. Thirteen (32.5%) patients were in REF-1 group, 9 (47.5%) were in group REF-2 and 8 (20%) were in group REF-3. Fifteen (37.5%) patients had good control of diabetes, 16 (40%) patients had fair control while 9 (22.5%) patients had poor control. Duration of diabetes varied from newly diagnosed (0 years) to 20 years with mean duration of 5.33 years (SD=4.73). Nine (22.5%) patients were recently diagnosed, 18 (45%) patients had disease span of 2 – 5 years while 13 (32.5%) patients had disease span of more than 5 years. Number of echogenic foci had significant and stronger association with disease span (p